2017
DOI: 10.1007/s13187-017-1295-3
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Survivorship Care Plan Utilization and Impact on Clinical Decision-Making at Point-of-Care Visits with Primary Care: Results from an Engineering, Primary Care, and Oncology Collaborative for Survivorship Health

Abstract: Every cancer survivor and his/her primary care provider should receive an individualized survivorship care plan (SCP) following curative treatment. Little is known regarding point-of-care utilization at primary care visits. We assessed SCP utilization in the clinical context of primary care visits. Primary care physicians and advanced practice providers (APPs) who had seen survivors following provision of an SCP were identified. Eligible primary care physicians and APPs were sent an online survey, evaluating S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…In a study of childhood cancer survivorship care, only 51% of PCPs sent an SCP as part of the study recalled receiving it ( 61 ). PCPs in a survey regarding primary care for adult breast cancer survivors reported being unaware of the SCP (73%), difficulty locating it (30%), and finding needed information faster via another mechanism (15%) ( 62 ). These barriers were reported even though SCPs are standardly housed in the EHR problem list within their institution.…”
Section: Resultsmentioning
confidence: 99%
“…In a study of childhood cancer survivorship care, only 51% of PCPs sent an SCP as part of the study recalled receiving it ( 61 ). PCPs in a survey regarding primary care for adult breast cancer survivors reported being unaware of the SCP (73%), difficulty locating it (30%), and finding needed information faster via another mechanism (15%) ( 62 ). These barriers were reported even though SCPs are standardly housed in the EHR problem list within their institution.…”
Section: Resultsmentioning
confidence: 99%
“…Using the EMR to care for survivors in the primary care setting has been difficult for PCPs as it is difficult to find these relevant documents and EMRs are not designed for survivorship care [ 43 ]. Of 88 PCPs surveyed who had received SCPs on their patients, most were unaware of the SCP in general (73%) and had difficulty locating it (30%) [ 44 ]. The same meta-analysis showed that most PCPs wanted to receive SCPs and used these in conversation with their patient, but the few studies which tracked PCP receipt and integration of SCP showed only 13% consistently received SCPs.…”
Section: Discussionmentioning
confidence: 99%
“…An initial questionnaire was developed by the authors based on literature about the side and long-term effects of cancer and cancer therapies. 2,36,37 The draft Care of Cancer Survivors questionnaire was reviewed and revised at a weekly research faculty meeting. The resulting 59-item questionnaire included 2 questions regarding patient demographics, 3 questions on office electronic medical record (EMR) capabilities, 10 questions on office policies regarding care of cancer survivors, 2 questions regarding physicians' awareness of history of persons with cancer in the office and how they knew of cancer survivorship status, 15 Likert-style questions on the physician's confidence managing mental health and side effects of cancer therapies, 13 questions regarding the availability of resources for cancer survivors, 5 questions on survivorship care, 3 questions on changes in psychosocial and physical health of cancer survivors and time frame of effects of cancer treatment, 3 questions on the concerns and barriers for cancer survivor patients, and 3 questions on the quality of life of the cancer survivors.…”
Section: Instrumentmentioning
confidence: 99%
“…The resulting 59-item questionnaire included 2 questions regarding patient demographics, 3 questions on office electronic medical record (EMR) capabilities, 10 questions on office policies regarding care of cancer survivors, 2 questions regarding physicians' awareness of history of persons with cancer in the office and how they knew of cancer survivorship status, 15 Likert-style questions on the physician's confidence managing mental health and side effects of cancer therapies, 13 questions regarding the availability of resources for cancer survivors, 5 questions on survivorship care, 3 questions on changes in psychosocial and physical health of cancer survivors and time frame of effects of cancer treatment, 3 questions on the concerns and barriers for cancer survivor patients, and 3 questions on the quality of life of the cancer survivors. 2,36 Office policy and EMR questions were modeled off another questionnaire the researchers had previously used. 37 Mailing A second duplicate mailing was sent to the nonresponders within 3 weeks of the first mailing.…”
Section: Instrumentmentioning
confidence: 99%